2021
DOI: 10.3892/or.2021.8088
|View full text |Cite
|
Sign up to set email alerts
|

Phlorizin from sweet tea inhibits the progress of esophageal cancer by antagonizing the JAK2/STAT3 signaling pathway

Abstract: Phlorizin, an important member of the dihydrochalcone family, has been widely used as a Chinese Traditional Medicine for treatment of numerous diseases. The present study aimed to investigate the potential therapeutic effects of phlorizin on esophageal cancer. Phlorizin, extracted from sweet tea, was used to treat esophageal cancer cells. Cell proliferation, migration and invasion were determined using Cell Counting Kit-8 and colony formation assays, and wound healing and Transwell assays, respectively. RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In addition, RNA sequencing technologies show that SQSTM1/p62 (autophagy markers) was upregulated in esophageal cancer cells after treatment with phlorizin, the main component of the sweet tea leaf (Lithocarpus polystachyus Rehd). These data suggest that phlorizin can inhibit autophagy in esophageal cancer by regulating the ubiquitin-binding protein SQSTM1/P62 (Jia et al, 2021).…”
Section: Genomicsmentioning
confidence: 75%
“…In addition, RNA sequencing technologies show that SQSTM1/p62 (autophagy markers) was upregulated in esophageal cancer cells after treatment with phlorizin, the main component of the sweet tea leaf (Lithocarpus polystachyus Rehd). These data suggest that phlorizin can inhibit autophagy in esophageal cancer by regulating the ubiquitin-binding protein SQSTM1/P62 (Jia et al, 2021).…”
Section: Genomicsmentioning
confidence: 75%
“…This study demonstrated that root bark glycosides antagonize the JAK2/STAT3 signaling pathway, which can inhibit the development of esophageal cancer. It has also been demonstrated that root bark glycosides promote apoptosis and inhibit autophagy in esophageal cancer cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the JAK2/STAT3 pathway plays a regulatory role in the growth, metastasis of esophageal cancer cells (Liu et al, 2015; Xu et al, 2020). For example, phlorizin from sweet tea inhibits the growth, migration, aggressiveness, autophagy, and induces the apoptosis of esophageal cancer cells by antagonizing JAK2/STAT3 signaling pathway (Jia et al, 2021). Dehydrocostus lactone facilitates the apoptosis and cell cycle arrest of esophageal cancer cells through JAK2/STAT3/PLK pathway (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%